Stability of formula Bacillus spp. for control Ralstonia syzygii subsp. Indonesiensis and increase the growth and the yield of chili plants - Nilisma, Muzilatul; Yanti, Yulmira; Habazar, Trimurti (International Journal of Environment, Agriculture and Biotechnology, 2020)
Solid formulations of Rhizobacteria Bacillus. Spp. and storage time to control bacterial wilt disease Ralstonia syzygii subsp. indonesiensis. Bacterial wilt disease caused by Ralstonia syzygii subsp. indonesiensis is a major constraint in chili cultivation. Bacillus spp,is capable to suppres bacterial wilt disease, to increase the growth and the yield of chili plants. The aim of this research was to obtain the best formula of Bacillus spp. which was stable to control bacterial wilt disease and to increase the growth and yield of chili plants. To increased its stability and interaction with chili plants, Bacillus spp, was urged to test furthermore especially its formulation with based on solid organic carriers (rice bran, rice straw, bagasse and their combination). The most effective storage time also need to test. Result showed that all formula had ability to decrease incidence of bacterial wilt disease compared to control. Moreover, all the three formula could increase plant growth, total of leaves, total of branch and yields. Decreasing of disease rate and increasing of plant growth rate variated between different formulations.